Collagen Type III and VI Remodeling Biomarkers Are Associated with Kidney Fibrosis in Lupus Nephritis. Issue 9 (30th September 2021) - Genovese, Federica; Akhgar, Ahmad; Lim, Sung Sam; Farris, Alton B.; Battle, Monica; Cobb, Jason; Sinibaldi, Dominic; Karsdal, Morten A.; White, Wendy I.
Visual Abstract: Abstract : Key Points: Prognostic biomarkers that identify patients with SLE at risk of developing lupus nephritis and progressing to kidney failure are needed. Tubulointerstitial fibrosis is an important pathologic feature of lupus nephritis and is associated with kidney disease progression. Circulatory and urinary markers of collagen type III and type VI remodeling noninvasively reflect levels of kidney fibrosis in patients with lupus nephritis. Background: Lupus nephritis (LN) occurs in <40% of patients with SLE. Reliable biomarkers of kidney damage are needed to identify patients with SLE at risk of developing LN to improve screening, treat the disease earlier, and halt progression to kidney failure. Novel biomarkers of extracellular matrix remodeling were evaluated as markers of kidney fibrosis and disease activity in patients with LN. Methods: Biomarkers of the interstitial collagen type III (PRO-C3) and type VI (PRO-C6) formation and of collagen type III (C3M) degradation were evaluated in the serum and urine of 40 patients with LN, 20 patients with SLE but without LN, 20 healthy controls, and ten biopsy controls (histologic kidney inflammation/damage without SLE). Their association with histologic markers of interstitial fibrosis and tubular atrophy, with inflammatory cell infiltration and with disease activity and chronicity in the patients with LN was assessed. Results: Despite PRO-C3 (serum) and PRO-C6 (serum and urine) being significantly elevated in patients with LN compared with healthy controls, the markers did not differentiate patients with LN from those with SLE. C3M (urine) levels were not different in LN compared with the other groups. C3M (urine) strongly correlated and PRO-C6 (serum and urine) inversely correlated with kidney function (eGFR). The biomarkers of interstitial collagen turnover PRO-C6 (serum) and C3M (urine) correlated with histologic markers of interstitial fibrosis, tubular atrophy, and monocyte infiltration. Conclusions: Noninvasive collagen turnover biomarkers are promising tools to identify patients with SLE with kidney histologic modifications.